G304(P) A case of relapsing polychondritis in a paediatric patient with severe airway involvement – the challenges of long term airway & respiratory management. (25th October 2020) - Kothari, T; Magnussen, E; Dawson, P; Al Abadi, E; Elloy, M; Sridhar, A; Kapoor, S; Bandi, S; Ahmed, I
Abstract : Background: Relapsing polychondritis (RP) in childhood is a rare multi-system disease characterised by inflammation of multiple cartilages. Progressive destruction of cartilaginous tissues in patients with tracheobronchial involvement can lead to life threatening exacerbations. Diagnosis in children and young people is often delayed due to rarity of this condition although the clinical course is often more severe than in adults with a higher incidence of laryngotracheobronchial involvement. Case Report: A 14-year-old of African descent presented to the children's hospital with evidence of auricular inflammation, anterior rib pain and red, painful eyes. She had raised inflammatory markers and was treated with broad-spectrum antibiotics. RP was suspected and high dose oral steroids were commenced, improving all symptoms. On weaning steroids, she quickly relapsed and presented with upper airway problems including stridor, barking cough and increased work of breathing. Initial flexible nasendoscopy showed interarytenoid and subglottic oedema and likely tracheobronchitis. She was commenced on Rituximab and a six-month course of Cyclophosphamide. CT Neck and thorax showed focal obliteration of the airway at the level of hypopharynx and narrowing of left main bronchus. CT bronchogram showed the narrowing improved on a PEEP of 12 cm H2O. She was trialled on BiPAP overnight which helped her symptoms. She was referred to Great Ormond Street Hospital for a review; no further changes in management were suggested. The patient had recurrent relapses needing intensive care, therefore she was started on methotrexate and adalimumab, and had a balloon dilatation for her subglottic oedema and stenosis, which she tolerated well. She has been discharged home on overnight BiPAP with a plan for monthly balloon dilatations with ENT and to continue on methotrexate and adalimumab with gradual wean of steroids. Conclusion: RP is rare with estimated incidence of 3.5 per million, only 10% cases are seen in paediatrics. Without aggressive and prompt treatment, life-threatening complications can develop rapidly, and outcomes are poor. Managing children with RP with significant airway involvement with NIV and repeated monthly balloon dilatations can help prevent life threatening exacerbations and the need for a tracheostomy. This case demonstrates the importance of multidisciplinary management of this complex condition.